The effect of project-based learning on writing skill for the seventh grades student - Nuraisyah Egilia; Erlik Widiyani Styati; Theresia Budi Sucihati (English Teaching Journal : A Journal of English Literature, Language and Education, 2023)
This study aims to know the effect of Project Based Learning to the students’ writing skill in descriptive text in the seventh-grade students of SMPN 3 Maospati in which the experimental research design was applied. The total of students are 30 hich is sample consisted of 14 males and 16 females students. The essay test of writing descriptive text was used to collect the data about the students’ writing skill before and after the treatments about teaching writing using project based learning. Then the data were analyzed using statistical formula of t-test computation. The result shown that the students’total score of experimental class post-test is 2170, and then total score of pre-test is 1758. It means that students’ score increased. Based on the data report of the table of t-test based on signification, the result of this research showed that T-score 0,003 < 0,05.  It means that was significant so the Null Hypothesis (Ho) was rejected and Alternative Hypothesis (Ha) was accepted. In conclusion, there is significant effect of teaching writing. It can be concluded that the Project Based Laearning (PJBL) method is not effective in teaching writing.